HISTORY OF FORMATION AND DEVELOPMENT OF THE MAIN LEGAL SYSTEMS (LEGAL FAMILIES) IN THE WORLD - Rozanova, Elizabeth; Stepanov, Mikhail; Alekseev , Igor; Aivazidis , Achilles; Prokoshin, Maxim (Revista Notas Históricas y Geográficas, 2021)
The relevance of the study of the formation and development of legal systems in the modern world is due to the increasingly complex development of legal systems in different countries. To understand the direction in which national legal systems and national legislation need to develop, it is necessary to rethink the legal families that have existed for centuries and understand the algorithms for their development, identifying new vectors for improving modern legal systems in different countries. Throughout the history of humanity, Roman law constantly changed under the influence of the cultures in which it was introduced, resulting in various legal systems. A mixture of Roman law and the canonical and local legal customs of continental Europe became the basis of the so-called Romano-Germanic legal family.